2022
DOI: 10.1002/jia2.26020
|View full text |Cite
|
Sign up to set email alerts
|

Facility‐based HIV self‐testing strategies may substantially and cost‐effectively increase the number of men and youth tested for HIV in Malawi: results from an individual‐based mathematical model

Abstract: Introduction Malawi is rapidly closing the gap in achieving the UNAIDS 95‐95‐95 targets, with 90% of people living with HIV in Malawi aware of their status. As we approach epidemic control, interventions to improve coverage will become more costly. There is, therefore, an urgent need to identify innovative and low‐cost strategies to maintain and increase testing coverage without diverting resources from other HIV services. The objective of this study is to model different combinations of facility‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Scaling up HIVST would require the formulation or adoption of HIVST policies and a considerable financial investment to roll out these policies, including commodity management. Recent research in Malawi has shown the potential of HIVST to expand testing coverage, while reducing human resource time and limiting the risk of screening PLHIV out, given the much higher sensitivity of antibody screening platforms compared to risk-based screening tools [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scaling up HIVST would require the formulation or adoption of HIVST policies and a considerable financial investment to roll out these policies, including commodity management. Recent research in Malawi has shown the potential of HIVST to expand testing coverage, while reducing human resource time and limiting the risk of screening PLHIV out, given the much higher sensitivity of antibody screening platforms compared to risk-based screening tools [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scaling up HIVST would require formulation or adoption of HIVST policies and a considerable financial investment to roll out these policies, plus commodity management. Recent research in Malawi has shown the potential of HIVST to expand testing coverage, while reducing HR time and limiting the risk of screening PLHIV out, given the much higher sensitivity of antibody screening platforms compared to risk-based screening tools (12).…”
Section: Discussionmentioning
confidence: 99%
“…Scaling up HIVST would require formulation or adoption of HIVST policies and a considerable financial investment to roll out these policies, plus commodity management. Recent research in Malawi has shown the potential of HIVST to expand testing coverage, while reducing human resource time and limiting the risk of screening PLHIV out, given the much higher sensitivity of antibody screening platforms compared to riskbased screening tools (17).…”
Section: Discussionmentioning
confidence: 99%